An exploratory examination of philanthropy in the New Zealand, Spanish and US wine industries - Sharon L. Forbes; Rosana Fuentes Fernández; Armand Gilinsky (Wine Economics and Policy, 2018)
This exploratory study provides an insight into the concept of philanthropy and how it is applied in the context of wineries. Researchers in three nations interviewed winery owners or managers to obtain qualitative data; this data was categorised to identify common themes, similarities and differences across wineries or nations. Our findings indicate that all the wineries are undertaking philanthropic activities, ranging from donations of wine, time, cash or facilities, to organising or participating in events. These activities are primarily driven by altruistic rather than strategic motivations, and the predominant benefits achieved from philanthropy are personal satisfaction rather than financial. Although only a small number of wineries were interviewed (11), this study of philanthropy is unique as it has examined both small and large businesses operating in a single industry sector, across multiple nations. Whilst the small sample is an obvious limitation of this study, future quantitative research with a larger sample will determine the degree to which these exploratory findings can be deemed to represent the global wine industry.
Keywords: 330; Benefits; Cross-cultural; Motives; Philanthropy; Wine industry